(untitled) - Baker, Donna L. (Indianapolis, IN, 2006)
Features comprehensive coverage and vital information that teaches readers all they need to know about the latest version of Photoshop Elements
Keywords: Photography,Nhiếp ảnh; Digital techniques,Kỹ thuật số